Gene Set Analysis: Challenges, Opportunities, and Future Research - Maleki, Farhad; Ovens, Katie; Hogan, Daniel J.; Kusalik, Anthony J. (Frontiers in Genetics, 2020)
Gene set analysis methods are widely used to provide insight into high-throughput gene expression data. There are many gene set analysis methods available. These methods rely on various assumptions and have different requirements, strengths and weaknesses. In this paper, we classify gene set analysis methods based on their components, describe the underlying requirements and assumptions for each class, and provide directions for future research in developing and evaluating gene set analysis methods.